Penerapan Peraturan Daerah Nomor 1 Tahun 2013 terhadap pemungutan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Kabupaten Halmahera Selatan - Baba, Rian M.; Sabijono, Harijanto; Rondonuwu, Sintje (Riset Akuntansi dan Portofolio Investasi, 2025)
The study’s objective is clear: to assess the implementation of Regional Regulation Number 1 of 2013 regarding the collection of Rural and Urban Land and Building Tax (PBB-P2) in South Halmahera Regency. We used a qualitative descriptive method through interviews and document analysis. The findings definitively show that the regulation has been applied in accordance with the stipulated tax collection procedures, including data collection, tax determination, and payment mechanisms. However, we have identified several obstacles, such as limited taxpayer awareness and administrative inefficiencies, which have contributed to persistent tax arrears. This research is vital for local governments to assess the effectiveness of existing taxation policies and identify obstacles faced by the government in implementing taxation policy.